Approximate Generalized Cubic *-Derivations. (20th November 2014) - Koh, Heejeong; Kang, Dongseung
Abstract : We will show the general solution of the functional equationf ( a x + b y ) + f ( a x - b y ) =a b 2 [ f ( x + y ) + f ( x - y ) ] + 2 a ( a 2 - b 2 ) f ( x ) and investigate the stability of cubic* -derivations associated with the given functional equation on Banach* -algebras.